2001
DOI: 10.4049/jimmunol.166.10.6311
|View full text |Cite
|
Sign up to set email alerts
|

Role of p190RhoGAP in β2 Integrin Regulation of RhoA in Human Neutrophils

Abstract: We found that engagement of β2 integrins on human neutrophils induced activation of RhoA, as indicated by the increased ratio of GTP:GTP + GDP recovered on RhoA and translocation of RhoA to a membrane fraction. The clustering of β2 integrins also induced a time-dependent increase in GDP bound to RhoA, which correlated with β2 integrin-induced activation of p190RhoGAP. The activation of p190RhoGAP was completely blocked by [4-amino-5-(4-methylphenyl)-7-(t-butyl)pyrazolo[3,4-d]pyrimidine] (PP1), a selective inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…Several observations support our conclusion. First, we have previously observed that engagement of ␤ 2 integrins on PMNs increased the activity of p190RhoGAP (a GAP protein for RhoA and Rac) and its translocation to a crude membrane fraction (22). Second, other investigators have detected Rac-GAP activity in a membrane fraction of PMNs and suggested that its modulation could play a role in the regulation of the NADPH oxidase (40).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Several observations support our conclusion. First, we have previously observed that engagement of ␤ 2 integrins on PMNs increased the activity of p190RhoGAP (a GAP protein for RhoA and Rac) and its translocation to a crude membrane fraction (22). Second, other investigators have detected Rac-GAP activity in a membrane fraction of PMNs and suggested that its modulation could play a role in the regulation of the NADPH oxidase (40).…”
Section: Figmentioning
confidence: 99%
“…We pretreated the PMNs with the following agents: wortmanin or LY294002, both of which inhibit PI 3-kinase by distinct mechanisms and are known to block fMLP-induced generation of phosphatidylinositol 3,4,5-trisphosphate and activation of the respiratory burst in PMNs (37), or PP1, which is a potent and selective inhibitor of Src family tyrosine kinases (38). We have previously shown that PP1 (3 M) blocks basal and ␤ 2 integrin-induced overall tyrosine phosphorylation of proteins in PMNs (22). In our present study, pretreatment of PMNs with wortmanin or LY294002 significantly reduced, but did not totally block, adhesion-induced up-regulation of Cdc42 activity, and it partly reversed adhesion-elicited down-regulation of the activities of Rac1 and Rac2 (Fig.…”
Section: ␤ 2 Integrin-mediated Regulation Of Rac and Cdc42mentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Although the regulatory function could be demonstrated both with human proteins and with murine cells, contribution of the protein to integrin activation differs in human and murine neutrophils. 12,13 In addition to phosphorylation, GAP activity can be altered in numerous other ways. 33 Neutrophils are characterized by a short lifetime (see Hellebrekers et al, in this issue); hence, expression-level regulation is not what one would typically expect.…”
Section: Arhgap25mentioning
confidence: 99%
“…Rac/Rho Human (cell free) NADPH oxidase [6,9,11] Mouse No role in integrin-mediated neutrophil functions and in rheumatoid arthritis [12] Human β2 integrin activation [13] ARHGAP46/GMIP RhoA Mouse/human Azurophilic granule exocytosis. [14] ARHGAP15 Rac Mouse Migration, NADPH oxidase, phagocytosis, abdominal sepsis, retention in bone marrow [15,16] Human/cell culture Migration, actin polymerization [17] ARHGAP13/srGAP1 Cdc42 Mouse/human Neutrophil chemotaxis [18] BCR/ABR Rac/Cdc42 Mouse (double knockout) Acute inflammatory responses [19] BCR Rac/Cdc42 Human (cell free) NADPH oxidase [9] Mouse Septic shock NADPH oxidase [20] ARHGAP12 Rac Human/cell culture Actin polymerization [8] ARHGAP43/SH3BP1 Rac Human/cell culture Actin polymerization [8] ARHGAP21/ ARHGAP10…”
Section: How Many Rho Family Gaps Are Involved In Organizing a Funcmentioning
confidence: 99%